Improving the nutritional status of tropical ruminants - MacMillan, Susan (1996)
Cattle, sheep, goats, buffalo and other ruminant animals in developing countries feed mainly on poor-quality plant material, on natural rangelands or pastures as well as on bushes, trees and crop residues. The efficient utilization of such materials depends upon symbiotic micro-organisms in one of the digestive compartments of these animals. A research project at the International Livestock Research Institute (ILRI), based in Kenya and Ethiopia, focuses on the ability of ruminants to utilize microbial organisms to produce good-quality protein. Understanding the rumen fermentation system will allow scientists to modify it to improve ruminant production.